PERCEPTION OF BOSNIA AND HERZEGOVINA'S QUALIFICATION TO FIFA WORLD CUP 2014 BY DIFFERENT ETHNIC GROUPS - Özgür Dirim Özkan (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: Generally, in Balkans, particularly in Bosnia and Herzegovina, football fandom is very much associated with the fact of ethnic tension. Football is often used as a metaphor for warfare, while in turn, during the Yugoslav Wars, ironically football terminology was used to metaphorise the significance of ethnic slaughtering. In fact, it is very commonly uttered that the starting flame of the Yugoslav Wars was sparkled in Zagreb Maksimir Stadium in May 13, 1990 after a match between Red Star Belgrade and Dinamo Zagreb. During the Yugoslav Wars, fan groups acted as recruitment agencies for organizing paramilitary groups who were convicted for organizing war crimes. This was the case in Bosnia as well. Although almost two decades have passed since the war in Bosnia, the effects of ethnic nationalism in football fandom is still inevitable. Recently, national football team of Bosnia succeeded to participate in the 2014 World Cup, which will be organized in Brazil, causing euphoria in the country. However, it is a controversial issue whether if all the ethnic groups, namely Bosnian Croats and Bosnian Serbs respectively did attend the celebrations. In other words, it is a question mark if they perceive Bosnian National Football as their "national" team. In this sense, this paper aims to discuss the perception of this success by different ethnic groups relying on interviews with different fan groups in the country. Methods: The presentation will rely on two basic resources: [1] An ethnographic study which was conducted in Bosnia in 2007/2008 as a part of PhD dissertation titled Football Fandom as a Factor Behind Formation of Cultural Differences: A Case Study on FK Sarajevo and FK Zeljeznicar Football Fans and ongoing observations of the presenter on Bosnian football since then. [2] Deep interviews with leading football fan groups of different clubs with different ethnic backgrounds like Velež Mostar, Čelik Zenica, Sloboda Tuzla (predominantly Bosnian Muslim), Zrinjski, Široki Brijeg (predominantly Bosnian Croat), Borac Banja Luka, FK Slavija (predominantly Bosnian Serb) which will be organized due to the start of the second half of the Premier League of Bosnia and Herzegovina by March 2014. Results: The results of the interviews will be analyzed at the end of the interviews. On the other side, it has been observed that Bosnian Serbs' and Bosnian Croats' perception of national team of BIH differs from Bosnian Muslims'. The paper will discuss this perceptional difference due to different dynamics of identity construction. Discussion: The discussion will discuss the inclusionist and exclusionist cultural dynamics and their effect on the process of identity formation. The concept of identity deriving from the Latin origin idem, which means "sameness" does not in fact only refer to absolute sameness, but also to differentiation. In this sense, it is not enough only to construct identity through similarities, but also it is important to construct differences as well. Constructing, or defining differences is not only important on how we define the others, but also how others define us. References: Duke V, Crolley L (1996) Football, Nationality and the State, 83-100. Giulianotti R (2003) Football: A Sociology of the Global Game, 1-39. Jenkins, R. (1996) Social Identity. Kuper S (2003). Futbol Asla Sadece Futbol Değildir (Football Against Enemey), 7-74. Wilson J (2006). Behind the Curtain: Travels in Eastern European Football, 98-183. Vrcan S, Lalic D (1999) From Ends to the Trenches, and Back: Football in the Former Yugoslavia (in Armstrong G, Giulianotti R, Football Cultures and Identities), 176-189.